The Role of Islamic Religious Education Teachers in Forming the Disciplinary Character of Junior High School Students - Harianto Harianto; Iin Kandedes (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2023)
This study aims to 1) determine the role of Islamic Religious Education teachers in forming the disciplinary character of Ruhama Islamic Middle School students; and 2) knowing the supporting factors and inhibiting factors in the formation of the disciplinary character of Ruhama Islamic Middle School students. The research method used is descriptive qualitative method and direct observation. The data collection techniques used by interviews, observation and documentation. Checking the validity of the data using source triangulation, technical triangulation and time. Data analysis was carried out in three stages, namely data reduction, data display, and conclusion/verification. The results of the study show that Islamic Religious Education, with the teacher as the subject, has a role in the formation of disciplinary character. Islamic Religious Education teachers who always teach by giving advice and motivation, do not forget to also reprimand and give educational punishments to students who break the rules. The use of existing learning methods and media is also maximized in conveying Islamic religious education material in class and training children's discipline, such as the question and answer method, discussion and group work. Apart from that, the core material of Islamic religious education can also be found in school activities such as Duha prayers, the habit of ablution and fardhu prayers on time. Then in an effort there must be supporting and inhibiting factors, as well as in Ruhama Islamic Middle School. In practice teachers, parents, peers and the community environment can be factors that support or hinder efforts to build this disciplinary character.